Museums and heritage tourism theory, practice and people - White, Chris 1966- (Routledge, 2023)
"White examines the symbiotic relationship between museums, heritage attractions, and tourism, using a range of international case studies. Divided into three clear sections, White first outlines a theoretical framework for understanding the role of museums in heritage tourism, before addressing practical challenges of interpretation, design, and pandemic response. Finally, he traces the development of museum and heritage attraction design through the key figures of John Ruskin, James Gardner and Alex McCuaig. Each chapter incorporates a key case study, with an international scope including examples from Hong Kong, the UK, Taiwan, Qatar, Dubai, and Kuwait. An essential introduction for undergraduate and graduate students taking courses in museum studies, heritage studies, and tourism management"--